The complete upmanship : including, Gamesmanship, Lifemanship, One-upmanship, Supermanship - Potter, Stephen, 1900-1969. (New York : Holt, Rinehart, and Winston, 1971)
Including : Gamesmanship, Lifemanship, One-upmanship, Supermanship.
Keywords: Conduct of life -- Humor